The impacts of community-based HIV testing and counselling on testing uptake - Jaelan Sumo Sulat; Yayi Suryo Prabandari; Rossi Sanusi; Elsi Dwi Hapsari; Budiono Santoso (College of Public Health Sciences, Chulalongkorn University, 2018)
Purpose - Community-based HIV testing and counselling (HTC) has been recommended for improving access to prevention, care, and treatment services in at-risk populations. Earlier systematic reviews and meta-analyses have been undertaken, but due to some methodological limitations, their findings do not yet provide a practical significance. The purpose of this paper is to re-examine the recent evidence of the efficacy of community-based HTC approaches on the uptake of HTC in at-risk populations. Design/methodology/approach - The database of PubMed online, Science Direct, the Lancet Global Health, the Cochrane Central Register of Controlled Trials, and Google Scholar were systematically searched using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines to obtain empirical papers published between March 2013 and December 2015. Findings - Of 600 collected papers, there were 6 cluster randomized trials papers which met the inclusion criteria. Compared to the health facilities-based HTC, community-based HTC approaches have been shown to improve the uptake of HIV testing from 5.8 to 37 per cent, and improve HIV testing in men and their partners together from 6.8 to 34 per cent. The community approaches also detected lower HIV-positive cases (0.29 per cent as compared to 4 per cent), improved access to treatment services from 0.3 to 25 per cent, demonstrated higher cluster differentiation 4 count in newly diagnosed patients (median of 400-438 cells/µl), and increased the rate of first-time HIV testing from 9 to 11.8 per cent. With respect to social and behavioural outcomes, community-based HTC increased social norms for HIV testing by 6 per cent (95 per cent CI 3-9), decreased multiple sex partners by 55 per cent (95 per cent CI 42-73), lowered casual sex by 45 per cent (95 per cent CI 33-62), increased knowledge about HIV (83.2 vs 28.9 per cent), improved positive attitudes towards HIV patients (73.0 vs 34.3 per cent), and increased the use of condoms (28.0 vs 12.3 per cent). Originality/value - Community-based HTC combined with behavioural interventions have been found to be more effective in increasing the uptake of HIV testing as well as other outcomes as compared to the conventional health facilities-based testing and counselling approaches.